A new protective role for S100A9 in regulation of neutrophil recruitment during invasive pneumococcal pneumonia. Issue 8 (28th April 2014) - De Filippo, Katia; Neill, Daniel R.; Mathies, Meg; Bangert, Mathieu; McNeill, Eileen; Kadioglu, Aras; Hogg, Nancy
Abstract : The S100A8/A9 heterodimer is abundantly expressed by myeloid cells, especially neutrophils, but its mechanism of action is only partially determined. In this study we investigated S100A8/A9 involvement in the host response to Streptococcus pneumoniae infection making use of S100a9 –/– mice that lack heterodimer expression in myeloid cells. S100a9 –/– mice that were infected intranasally with pneumococci rapidly succumbed, with 80% mortality after 48 h, whereas the majority of wild‐type mice recovered. Over this time period, S100a9 –/– mice displayed an average 6‐fold reduction in circulating and lung‐recruited neutrophils. Taqman analysis of S100a9 –/– lungs revealed decreased production of a dominant subset of 5 cytokines and chemokines associated with neutrophil recruitment. The greatest differential was with the cytokine granulocyte colony‐stimulating factor (G‐CSF) that causes bone marrow release of neutrophils into the circulation (1900‐fold difference at 48 h). Treating S100a9 –/– mice with G‐CSF reversed their increased susceptibility to infection by enhancing both circulating neutrophils and neutrophil recruitment into infected lungs, by reducing pneumococcal colony forming units, and by elevation of chemokine CXCL1, cytokine IL‐6, and endogenous G‐CSF proteins. Thus S100A9, potentially with its partner S100A8, makes a major contribution in the host response to pneumococcal infection by increasing circulating neutrophils principally regulation of G‐CSF production.—De Filippo, K., Neill, D. R., Mathies, M., Bangert, M., McNeill, E., Kadioglu, A., Hogg, N. A new protective role for S100A9 in regulation of neutrophil recruitment during invasive pneumococcal pneumonia. FASEB J. 28, 3600–3608 (2014). www.fasebj.org